2006
DOI: 10.1128/jvi.80.1.460-473.2006
|View full text |Cite
|
Sign up to set email alerts
|

Nonstructural Protein 3 of Bluetongue Virus Assists Virus Release by Recruiting ESCRT-I Protein Tsg101

Abstract: The release of Bluetongue virus (BTV) and other members of the Orbivirus genus from infected host cells occurs predominantly by cell lysis, and in some cases, by budding from the plasma membrane. Two nonstructural proteins, NS3 and NS3A, have been implicated in this process. Here we show that both proteins bind to human Tsg101 and its ortholog from Drosophila melanogaster with similar strengths in vitro. This interaction is mediated by a conserved PSAP motif in NS3 and appears to play a role in virus release. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(133 citation statements)
references
References 81 publications
(92 reference statements)
4
129
0
Order By: Relevance
“…Recent studies have revealed that viral matrix proteins play critical roles during the later stages of virus budding in many enveloped RNA viruses, including retroviruses, rhabdoviruses, filoviruses and orthomyxoviruses; these viral proteins possess a so-called late (L)-domain containing PT/SAP, PPXY and YXXL, which are critical motifs for efficient budding (Bouamr et al, 2003;Ciancanelli & Basler, 2006;Göttlinger et al, 1991;Harty et al, 1999Harty et al, , 2000Wirblich et al, 2006). The PTAP motif was first identified in HIV Gag and has been reported to bind to Tsg101, which functions in vacuolar protein sorting (Garrus et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that viral matrix proteins play critical roles during the later stages of virus budding in many enveloped RNA viruses, including retroviruses, rhabdoviruses, filoviruses and orthomyxoviruses; these viral proteins possess a so-called late (L)-domain containing PT/SAP, PPXY and YXXL, which are critical motifs for efficient budding (Bouamr et al, 2003;Ciancanelli & Basler, 2006;Göttlinger et al, 1991;Harty et al, 1999Harty et al, , 2000Wirblich et al, 2006). The PTAP motif was first identified in HIV Gag and has been reported to bind to Tsg101, which functions in vacuolar protein sorting (Garrus et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…NS3 functions as a viroporin, facilitating virus release by inducing membrane permeabilization [33]. In addition, NS3 binds to the cellular protein Tsg101 [104], allowing BTV particles to also leave host cells by a budding mechanism, similarly to retroviruses. This budding mechanism might be involved in BTV egress from insect cells in which BTV does not induce significant cytopathic effect, whereas the viroporin mechanism would be more prominent in mammalian cells.…”
Section: Ns3mentioning
confidence: 99%
“…However, some cell types that support the replication of the virus do not demonstrate a cytopathic effect to BTV, such as insect cells [73], T cell lines [96] and activated blood lymphocytes [5]. The budding versus the viroporin-mediated viral exit mechanism might partially explain this difference [104].…”
Section: Cell Deathmentioning
confidence: 99%
“…NS3 is a viroporin-like protein, facilitating virus release by membrane permeabilization (Han & Harty, 2004). It interacts with the calpactin light chain p11 of the cellular annexin II complex and with cellular Tsg101 at its N terminus (Beaton et al, 2002;Celma & Roy, 2011), which are involved in membrane-related events, secretion and intracellular trafficking (Raynal & Pollard, 1994;Wirblich et al, 2006). BTV NS3 also contains highly conserved PSAP and PPXY late domain motifs common in Tsg101-recruiting proteins (Wirblich et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It interacts with the calpactin light chain p11 of the cellular annexin II complex and with cellular Tsg101 at its N terminus (Beaton et al, 2002;Celma & Roy, 2011), which are involved in membrane-related events, secretion and intracellular trafficking (Raynal & Pollard, 1994;Wirblich et al, 2006). BTV NS3 also contains highly conserved PSAP and PPXY late domain motifs common in Tsg101-recruiting proteins (Wirblich et al, 2006). The C-terminal cytoplasmic domain interacts with the outer capsid protein VP2 (Beaton et al, 2002), suggesting that NS3 supports virus release by connecting virus to cellular transport mechanisms and by disruption of the cell membrane.…”
Section: Introductionmentioning
confidence: 99%